(untitled) (Revista de Ciências Agroveterinárias, 2019)
The collage on pieces of wood using adhesives has been performed since the Pharaoh era. Over the years, technologies have been developed especially for adhesives and different species of wood, adapting to the desired diverse uses. In this context we can also infer the methods of analysis and its efficiency. The aim of this study was to evaluate the resistance in the glue-line by using adhesives in Paulownia tomentosa wood (Japanese kiri). The bonded joints were prepared with resorcinol formaldehyde and melamine urea formaldehyde adhesives. The wood-adhesive interface was evaluated by means of the thickness of the main and secondary glue-lines using photomicrographs, shear strength, and percentage of wood imperfections. The adhesives presented non-uniform behavior in the glue-line. It was possible to observe that the adhesives penetrated in the wood anatomical structures (elements of vessels and rays). The resorcinol formaldehyde adhesive had higher penetration values. The kiri wood imperfection percentage was greater than 92%, independent of the adhesive. The high efficiency observed in bonding with both adhesives allows the use of wood of Paulownia tomentosa in Brazil for furniture and civil construction.